On the logic of communicative acts - Plunze, Christoan (Proceedings of the Amsterdam Colloquium, 2007)
In this paper I answer the question how it could be that someone already communicates if his or her communicative intention is recognized by an addressee — without relying on the somewhat mysterious assumption that the recognition of a communicative intention implies somehow the fulfillment of this intention.